Clariel eaudiobook The lost abhorsen. - Nix, Garth (The Old Kingdom, 2014)
The long-awaited fourth audiobook in the  New York Times  bestselling Old Kingdom series by Garth Nix. Award-winning author Garth Nix returns to the Old Kingdom with a thrilling prequel complete with dark magic, royalty, dangerous action, a strong heroine, and flawless world-building. This epic fantasy adventure is destined to be a classic, and is perfect for fans of  Game of Thrones . Clariel is the daughter of one of the most notable families in the Old Kingdom, with blood relations to the Abhorsen and, most important, to the King. She dreams of living a simple life but discovers this is hard to achieve when a dangerous Free Magic creature is loose in the city, her parents want to marry her off to a killer, and there is a plot brewing against the old and withdrawn King Orrikan. When Clariel is drawn into the efforts to find and capture the creature, she finds hidden sorcery within herself, yet it is magic that carries great dangers. Can she rise above the temptation of power, escape the unwanted marriage, and save the King?